2011
DOI: 10.1007/s11274-011-0872-6
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy, purification and chemical characterization of four bioactive compounds from new Streptomyces sp. TN256 strain

Abstract: A new actinomycete strain designated TN256, producing antimicrobial activity against pathogenic bacteria and fungi, was isolated from a Tunisian Saharan soil. Morphological and chemical studies indicated that strain TN256 belonged to the genus Streptomyces. Analysis of the 16S rDNA sequence of strain TN256 showed a similarity level ranging between 99.79 and 97.8% within Streptomyces microflavus DSM 40331(T) and Streptomyces griseorubiginosus DSM 40469(T) respectively. The comparison of its physiological charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…In this study, the natural product gave an optical rotation of []D -138.2 (c = 1.0, EtOH) which was compatible with those isolated earlier from other Streptomyces strains (Jain et al, 1977). This diketopiperazine (DKP) derivative compound is naturally produced by many organisms and displays a wide diversity of structures and biological functions (Smaoui et al, 2012). This scenario suggests that Gancidin W may be a useful chemical entity for the discovery and development of new drugs.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the natural product gave an optical rotation of []D -138.2 (c = 1.0, EtOH) which was compatible with those isolated earlier from other Streptomyces strains (Jain et al, 1977). This diketopiperazine (DKP) derivative compound is naturally produced by many organisms and displays a wide diversity of structures and biological functions (Smaoui et al, 2012). This scenario suggests that Gancidin W may be a useful chemical entity for the discovery and development of new drugs.…”
Section: Discussionsupporting
confidence: 84%
“…Cain et al 44 reported that cyclo(Pro-Tyr) exhibits no activity against strains of Micrococcus luteus, Mycobacterium smegmatis, Sacharomyces cerevisiae, Candida neoformans, Candida albicans and Aspergillus niger. Smaoui et al 45 reported the antimicrobial activity of Cyclo(Pro-Tyr) against Micrococcus luteus LB 14110, S. enterica ATCC43972 and Fusarium sp. Cyclo(Pro-Tyr) demonstrated inhibitory effects against bioluminescence by V. harveyi 46 .…”
Section: Discussionmentioning
confidence: 99%
“…This observation strongly suggested that the leucine unit of 1 was replaced by the 4hydroxyphenylanaline moiety in 5. Comparison with the literature, [10][11][12] compound 5 was identified as Cyclo-(Pro-Tyr). This cyclodipeptide had antibacterial activity against both Gram-positive and Gram-negative bacteria and antifungal property.…”
Section: Extraction and Isolationmentioning
confidence: 85%